Can CHA2DS2-VASc and HAS–BLED Foresee the Presence of Cerebral Microbleeds, Lacunar and Non-Lacunar Infarcts in Elderly Patients With Atrial Fibrillation? Data From Strat–AF Study - Bianconi, Elisa; Del Freo, Giulia; Salvadori, Emilia; Barbato, Carmen; Formelli, Benedetta; Pescini, Francesca; Pracucci, Giovanni; Sarti, Cristina; Cesari, Francesca; Chiti, Stefano; Diciotti, Stefano; Gori, Anna Maria; et al. (Frontiers in Neurology, 2022)
Anticoagulants reduce embolic risk in atrial fibrillation (AF), despite increasing hemorrhagic risk. In this context, validity of CHA2DS2-VASc and HAS-BLED scales, used to respectively evaluate thrombotic and hemorrhagic risks, is incomplete. In AF patients, brain MRI has led to increased detection of ‘asymptomatic’ brain changes, particularly those related to small vessel disease, which also represent the pathologic substrate of intracranial hemorrhage, and silent brain infarcts, which are considered risk factors for ischemic stroke. Routine brain MRI in asymptomatic AF patients is yet not recommended. Our aim was to test predictive ability of risk stratification scales on the presence of cerebral microbleeds, lacunar and non-lacunar infarcts in 170 elderly AF patients on oral anticoagulants. Ad hoc developed R algorithms were used to evaluate CHA2DS2-VASc and HAS-BLED sensitivity and specificity on the prediction of cerebrovascular lesions: 1) maintaining original items’ weights; 2) augmenting weights’ range; 3) adding cognitive, motor, and depressive scores. Accuracy was poor for each outcome considering both scales either in phase 1 or 2. Accuracy was never improved by the addition of cognitive scores. The addition of motor and depressive scores to CHA2DS2-VASc improved accuracy for non-lacunar infarcts (sensitivity=0.70, specificity=0.85), and sensitivity for lacunar-infarcts (sensitivity=0.74, specificity=0.61). Our results are a very first step toward the attempt to identify those elderly AF patients who would most benefit from brain MRI in risk stratification.